2016
DOI: 10.1002/cctc.201600953
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Tuning the Acid–Base Properties of Boron‐Doped Magnesium Oxide Catalyst for the Selective Aldol Condensation

Abstract: Controlled incorporation of dopants into the structure of metal oxide catalysts can be used to fine‐tune their topological, chemical, and electronic properties. Conventional preparation methods (coprecipitation and impregnation) tend to produce materials with a limited extent of chemical interaction between metal oxide and dopant, small pore volume, and disconnected pore structure. Herein, we describe a combustion method to optimize both the porous structure of metal oxides and the chemical interaction with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…A reaction that has been extensively used for this purpose is the aldol condensation. , This reaction has been recently included in the design of many biomass-processing schemes, and its study has provided clear examples of complex behaviors, such as acid–base cooperativity. Several groups have investigated the effects of different types of acidic sites on the activity of immobilized base catalysts, demonstrating that cooperativity is affected by the strength, relative position, and structure of acid and base functionalities. , , Additional studies have shown the role of properties more relevant to interfacial interactions such as the effects of support hydrophobicity , and solvents on the reaction. ,, For example, it has been shown that the catalytic activity of amine-functionalized mesoporous silicas decreases with increasing solvent polarity. , This drop in activity has been attributed to the increasing stabilization of ion pairs formed between acidic groups and amines that blocks a fraction of the active sites by turning them into non-nucleophilic ammonium cations. ,, Interestingly, in spite of its high dielectric constant, water deviates from this trend: the catalytic activity of primary amines is higher in water than in methanol. , This anomalous behavior has been explained by the role of water in limiting competing reactions such as the formation of the non-enolizable Schiff base 1 (pathway a, Scheme ) , and the conjugated dehydration product 2 (pathway b, Scheme ) that deactivate another fraction of the active amine sites. In addition, water is required for the hydrolytic desorption of the product in the last step of the reaction (step c, Scheme ), which drives the equilibrium toward completion …”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…A reaction that has been extensively used for this purpose is the aldol condensation. , This reaction has been recently included in the design of many biomass-processing schemes, and its study has provided clear examples of complex behaviors, such as acid–base cooperativity. Several groups have investigated the effects of different types of acidic sites on the activity of immobilized base catalysts, demonstrating that cooperativity is affected by the strength, relative position, and structure of acid and base functionalities. , , Additional studies have shown the role of properties more relevant to interfacial interactions such as the effects of support hydrophobicity , and solvents on the reaction. ,, For example, it has been shown that the catalytic activity of amine-functionalized mesoporous silicas decreases with increasing solvent polarity. , This drop in activity has been attributed to the increasing stabilization of ion pairs formed between acidic groups and amines that blocks a fraction of the active sites by turning them into non-nucleophilic ammonium cations. ,, Interestingly, in spite of its high dielectric constant, water deviates from this trend: the catalytic activity of primary amines is higher in water than in methanol. , This anomalous behavior has been explained by the role of water in limiting competing reactions such as the formation of the non-enolizable Schiff base 1 (pathway a, Scheme ) , and the conjugated dehydration product 2 (pathway b, Scheme ) that deactivate another fraction of the active amine sites. In addition, water is required for the hydrolytic desorption of the product in the last step of the reaction (step c, Scheme ), which drives the equilibrium toward completion …”
Section: Introductionmentioning
confidence: 61%
“…Several groups have investigated the effects of different types of acidic sites on the activity of immobilized base catalysts, demonstrating that cooperativity is affected by the strength, relative position, and structure of acid and base functionalities. 19,[21][22][23][24][25][26][27][28][29]37 Additional studies have shown the role of properties more relevant to interfacial interactions such as the effects of support hydrophobicity 24,38−40 and solvents on the reaction. 18,19,41−43 For example, it has been shown that the catalytic activity of amine-functionalized mesoporous silicas decreases with increasing solvent polarity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To selectively convert the C 2 aldehydes into the corresponding C 4 coupling products (Scheme b) we have developed a number of catalytic systems based on basic K/Na‐X and K/Na‐Y, and MgO‐K/NaX, zeolites as well as B‐doped MgO oxides . The Mg‐Al Hydrotalcite, Al‐Beta zeolite, which along with the Mg‐B catalyst previously employed have shown the highest C 4 productivities among all the catalysts investigated, with productivities of 8.3, 23.4, and 24.2 mmol of C 4 g cat −1 h −1 , respectively, at 50–60 % conversion level and 180 °C (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…To selectively convert the C 2 aldehydes into the corresponding C 4 coupling products (Scheme 1 b) we have developed a number of catalytic systems based on basic K/Na-X and K/Na-Y, [11] and MgO-K/NaX, [12] zeolites as well as Bdoped MgO oxides. [13] The Mg-Al Hydrotalcite, Al-Beta zeolite, which along with the Mg-B catalyst previously employed have shown the highest C 4 productivities among all the catalysts investigated, with productivities of 8.3, 23.4, and 24.2 mmol of C 4 g cat À1 h À1 , respectively, at 50-60 % conversion level and 180 8C (Table S2). Notably, on the 7.5 wt.…”
mentioning
confidence: 93%
“…We employed 13 C-NMR for product identification and HPLC for quantification. The results showed that before reaction only the crotonic acid can be detected by 13 C-NMR ( Figure S2). After 3 h of reaction at pH 2.9 additional chemical shifts appeared in the 13 C-NMR spectra that corresponded to the formation of the epoxide (3methyloxirane-2-carboxylic acid) and a,b-dihydroxy acid (2,3-dihydroxybutanoic acid).…”
mentioning
confidence: 99%